Evaluation of The Effectiveness of Fall Prevention Interventions In The Elderly Population: A Literature Review - Awal, Moni; Nasela, Sitti Johri; Claartje, Masrikat Maya Diana; Peluw, Zulfikar (International Conference on Health Sciences, 2026)
Background: Falls are a multifactorial geriatric issue, with a global prevalence of 28–42% among individuals aged 70 and older. In Indonesia, the incidence rate ranges from 20–40%, increasing the financial burden on the healthcare system and diminishing the quality of life for the elderly. Aim: This study aims to evaluate the effectiveness of various fall-prevention interventions and identify the most effective strategies for reducing fall risk in the elderly. Methods: This study utilises a systematic narrative synthesis design of 9 primary studies published between 2020 and 2025. Data were collected from PubMed and Google Scholar databases using specific keywords and Boolean operators. Inclusion criteria focused on studies evaluating physical and digital interventions in the elderly population (aged 65 years). Results: The analysis indicates that structured physical exercise (such as balance and muscle-strengthening exercises) is the most effective strategy, significantly reducing fall risk. It was also found that integrating digital technology (such as motion-monitoring sensors) increased exercise adherence by 15–20%. However, a discrepancy exists between evidence-based prevention program targets and the actual risk profiles of the elderly in the field, with high-risk groups often not receiving adequate resource allocation. Conclusion: Effective fall prevention requires a multifactorial approach that combines routine physical exercise, periodic risk screening, and digital technology support. Optimising resource allocation for high-risk populations is crucial for program success. Limitations: This review is limited to open-access studies in English and Indonesian, potentially excluding relevant data from subscription-based journals.